Student Evaluations of Teaching Encourages Poor Teaching and Contributes to Grade Inflation: A Theoretical and Empirical Analysis - Stroebe, Wolfgang (Basic and applied social psychology, 2020)
Student Evaluations of Teaching (SETs) do not measure teaching effectiveness, and their widespread use by university administrators in decisions about faculty hiring, promotions, and merit increases encourages poor teaching and causes grade inflation. Students need to get good grades, and faculty members need to get good SETs. Therefore, SETs empower students to shape faculty behavior. This power can be used to reward lenient-grading instructors who require little work and to punish strict-grading instructors. This article reviews research that shows that students (a) reward teachers who grade leniently with positive SETs, (b) reward easy courses with positive SETs, and (c) choose courses that promise good grades. The study also shows that instructors want (and need) good SETs.